골다공증 환자의 Digital 방사선 요추 Image를 이용한 영상분석 - 박형후(Hyong-Hu Park); 이진수(Jin-Soo Lee) (한국콘텐츠학회 논문지, 14(11), 2014)
This study aimed to propose an accurate diagnostic method for osteoporosis by realizing a computer-aided diagnosis system with the application of the statistical analysis of texture features using digital images of lateral lumbar spine of patients with osteoporosis and providing reliable supplementary diagnostic information by model experimental research for early diagnosis of diseases. For these purposes, digital images of lateral lumbar spine of normal individuals and patients with osteoporosis were used in the experiments, and the values of statistical texture features on the set ROI were expressed in six parameters. Among the texture feature values of the six parameters of osteoporosis, the highest and lowest recognition rates of 95 and 80% were shown in average gray level and uniformity, respectively. Moreover, all the six parameters showed recognition rates of over 80% for osteoporosis: 82.5% in average contrast, 90% in smoothness, 87.5% in skewness, and 87.5% in entropy. Therefore, if a program developing into a computer-aided diagnosis system for medical images is coded based on the results of this study, it is considered possible to be applied to preliminary diagnostic data for automatic detection of lesions and disease diagnosis using medical images, to provide information for definite diagnosis of diseases, to diagnose by limited device, and to be used to shorten the time to analyze medical images. 본 연구는 골다공증 환자의 Digital 요추 측부 영상을 이용하여 질감특징의 통계적 분석으로 컴퓨터 보조진단 시스템 구현과 질병의 조기진단 및 치료를 위한 실험적인 모형 연구로 신뢰성 있는 보조적 진단 정보를 제공함으로써 골다공증에 대한 정확한 진단 방향을 제시하고자 하였다. 이를 위해서 정상인의 Digital 방사선 요추 측부 영상과 골다공증 환자의 Digital 방사선 요추 측부 영상을 실험 영상으로 하여 설정된 ROI에 대한 통계적 질감특징 값을 6가지 parameter로 나타냈다. 골다공증에 대한 질감특징분석 값 중 Average Gray Level에서 95%로 최고 높은 인식률을 나타내었고, Uniformity에서 80%로 가장 낮은 인식률을 나타내었다. 또한 Average Contrast에서 82.5%, Smoothness에서 90%, Skewness에서 87.5%, Entropy에서 87.5%를 나타내어 6가지 Parameter에서 모두 80%이상의 높은 인식률을 나타내 알고리즘의 안정성을 입증하였다. 따라서 본 연구 결과를 토대로 의료영상의 컴퓨터자동진단 시스템으로 발전된 프로그램을 coding 한다면 의료영상의 병소부위 자동검출, 질병 진단을 위한 예비 진단자료, 질병의 확진을 위한 자료제공, 제한된 장비로도 진단 가능, 의료영상의 판독시간 단축에 유용하게 사용될 수 있으리라 사료된다.